Pregunta
upstudy study bank question image url

2. Complete the following. a) Simplify \( \left(\frac{x}{2}-\frac{5}{x}\right)^{2} \). b) Calculate the value of \( \frac{x^{2}}{4}+\frac{25}{x^{2}} \), if \( \frac{x}{2}-\frac{5}{x}=3 \). 3. Complete the following. a) Simplify \( \left(\frac{x}{3}-\frac{6}{x}\right)^{2} \). b) Then evaluate \( \frac{x^{2}}{9}+\frac{36}{x^{2}} \), if \( \frac{x}{3}-\frac{6}{x}=1 \).

Ask by Klein Gross. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

**Solutions:** 1. **Problem 2:** - **2.a)** \( \left(\frac{x}{2} - \frac{5}{x}\right)^2 = \frac{x^2}{4} - 5 + \frac{25}{x^2} \) - **2.b)** \( \frac{x^{2}}{4} + \frac{25}{x^{2}} = 14 \) 2. **Problem 3:** - **3.a)** \( \left(\frac{x}{3} - \frac{6}{x}\right)^2 = \frac{x^2}{9} - 4 + \frac{36}{x^2} \) - **3.b)** \( \frac{x^{2}}{9} + \frac{36}{x^{2}} = 5 \)

Solución

Sure, let's solve each part step by step. --- ## Problem 2 ### 2.a) Simplify \( \left(\frac{x}{2} - \frac{5}{x}\right)^{2} \) **Solution:** We can use the algebraic identity for squaring a binomial: \[ (a - b)^2 = a^2 - 2ab + b^2 \] Let \( a = \frac{x}{2} \) and \( b = \frac{5}{x} \). Applying the identity: \[ \left(\frac{x}{2} - \frac{5}{x}\right)^2 = \left(\frac{x}{2}\right)^2 - 2 \cdot \frac{x}{2} \cdot \frac{5}{x} + \left(\frac{5}{x}\right)^2 \] Now, calculate each term: 1. **First Term:** \[ \left(\frac{x}{2}\right)^2 = \frac{x^2}{4} \] 2. **Second Term:** \[ 2 \cdot \frac{x}{2} \cdot \frac{5}{x} = 2 \cdot \frac{5}{2} = 5 \] Since it's subtracted in the original identity: \[ -2ab = -5 \] 3. **Third Term:** \[ \left(\frac{5}{x}\right)^2 = \frac{25}{x^2} \] **Combined Simplification:** \[ \left(\frac{x}{2} - \frac{5}{x}\right)^2 = \frac{x^2}{4} - 5 + \frac{25}{x^2} \] --- ### 2.b) Calculate the value of \( \frac{x^{2}}{4} + \frac{25}{x^{2}} \), if \( \frac{x}{2} - \frac{5}{x} = 3 \) **Solution:** From part 2.a, we have: \[ \left(\frac{x}{2} - \frac{5}{x}\right)^2 = \frac{x^2}{4} + \frac{25}{x^2} - 5 \] Given that: \[ \frac{x}{2} - \frac{5}{x} = 3 \] Square both sides: \[ \left(\frac{x}{2} - \frac{5}{x}\right)^2 = 3^2 = 9 \] Substitute back: \[ \frac{x^2}{4} + \frac{25}{x^2} - 5 = 9 \] Solve for \( \frac{x^2}{4} + \frac{25}{x^2} \): \[ \frac{x^2}{4} + \frac{25}{x^2} = 9 + 5 = 14 \] **Answer:** \( \frac{x^{2}}{4} + \frac{25}{x^{2}} = 14 \) --- ## Problem 3 ### 3.a) Simplify \( \left(\frac{x}{3} - \frac{6}{x}\right)^{2} \) **Solution:** Again, use the binomial square identity: \[ (a - b)^2 = a^2 - 2ab + b^2 \] Let \( a = \frac{x}{3} \) and \( b = \frac{6}{x} \). Applying the identity: \[ \left(\frac{x}{3} - \frac{6}{x}\right)^2 = \left(\frac{x}{3}\right)^2 - 2 \cdot \frac{x}{3} \cdot \frac{6}{x} + \left(\frac{6}{x}\right)^2 \] Now, calculate each term: 1. **First Term:** \[ \left(\frac{x}{3}\right)^2 = \frac{x^2}{9} \] 2. **Second Term:** \[ 2 \cdot \frac{x}{3} \cdot \frac{6}{x} = 2 \cdot \frac{6}{3} = 2 \cdot 2 = 4 \] With the negative sign from the identity: \[ -2ab = -4 \] 3. **Third Term:** \[ \left(\frac{6}{x}\right)^2 = \frac{36}{x^2} \] **Combined Simplification:** \[ \left(\frac{x}{3} - \frac{6}{x}\right)^2 = \frac{x^2}{9} - 4 + \frac{36}{x^2} \] --- ### 3.b) Evaluate \( \frac{x^{2}}{9} + \frac{36}{x^{2}} \), if \( \frac{x}{3} - \frac{6}{x} = 1 \) **Solution:** From part 3.a, we have: \[ \left(\frac{x}{3} - \frac{6}{x}\right)^2 = \frac{x^2}{9} + \frac{36}{x^2} - 4 \] Given that: \[ \frac{x}{3} - \frac{6}{x} = 1 \] Square both sides: \[ \left(\frac{x}{3} - \frac{6}{x}\right)^2 = 1^2 = 1 \] Substitute back: \[ \frac{x^2}{9} + \frac{36}{x^2} - 4 = 1 \] Solve for \( \frac{x^2}{9} + \frac{36}{x^2} \): \[ \frac{x^2}{9} + \frac{36}{x^2} = 1 + 4 = 5 \] **Answer:** \( \frac{x^{2}}{9} + \frac{36}{x^{2}} = 5 \) ---

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Extra Insights

To simplify \( \left(\frac{x}{2}-\frac{5}{x}\right)^{2} \): We start by expanding the square: \[ \left(\frac{x}{2}-\frac{5}{x}\right)^{2} = \left(\frac{x}{2}\right)^{2} - 2 \cdot \frac{x}{2} \cdot \frac{5}{x} + \left(-\frac{5}{x}\right)^{2} = \frac{x^{2}}{4} - 5 + \frac{25}{x^{2}}. \] So, the simplified form is: \[ \frac{x^{2}}{4} - 5 + \frac{25}{x^{2}}. \] Now to calculate \( \frac{x^{2}}{4}+\frac{25}{x^{2}} \), given \( \frac{x}{2}-\frac{5}{x}=3 \): From the given equation, rearranging gives: \[ \frac{x}{2} = 3 + \frac{5}{x}, \] Multiplying both sides by \( 2x \) results in: \[ x^{2} = 6x + 10 \Rightarrow x^{2} - 6x - 10 = 0. \] Using the quadratic formula: \[ x = \frac{6 \pm \sqrt{(-6)^{2} - 4(1)(-10)}}{2(1)} = \frac{6 \pm \sqrt{56}}{2} = 3 \pm \sqrt{14}. \] Now substitute \( x^{2} = 4(3 + \sqrt{14})(3 - \sqrt{14})\): Calculating, we find \( \frac{x^{2}}{4} + \frac{25}{x^{2}} = 6 + \frac{25}{10} = 6 + 2.5 = 8.5. \) --- To simplify \( \left(\frac{x}{3}-\frac{6}{x}\right)^{2} \): When expanding this expression, we get: \[ \left(\frac{x}{3}-\frac{6}{x}\right)^{2} = \left(\frac{x}{3}\right)^{2} - 2 \cdot \frac{x}{3} \cdot \frac{6}{x} + \left(-\frac{6}{x}\right)^{2} = \frac{x^{2}}{9} - 4 + \frac{36}{x^{2}}. \] Thus, the simplified expression is: \[ \frac{x^{2}}{9} - 4 + \frac{36}{x^{2}}. \] Next, to evaluate \( \frac{x^{2}}{9}+\frac{36}{x^{2}} \) when \( \frac{x}{3}-\frac{6}{x}=1 \): From the equation given, rearranging gives: \[ \frac{x}{3} = 1 + \frac{6}{x}. \] Multiplying through by \( 3x \) yields: \[ x^{2} = 3x + 18 \Rightarrow x^{2} - 3x - 18 = 0. \] Using the quadratic formula, we have: \[ x = \frac{3 \pm \sqrt{(3)^{2} + 4(18)}}{2} = \frac{3 \pm \sqrt{81}}{2} = \frac{3 \pm 9}{2}. \] Solving gives \( x = 6 \) or \( x = -3 \). Substituting \( x^{2} = 36 \), we find: \[ \frac{x^{2}}{9} + \frac{36}{x^{2}} = 4 + 1 = 5. \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad